AN INVESTIGATION OF STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARY - Irma Wahyuni; Meita Lesmiaty Khasyar; Novia Anggraeni (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2021)
Vocabulary is an essential building block of language and as such it makes sense to be able to measure learners’ knowledge of it. The objectives of the research is to know what are the difficulties faced by students in learning vocabulary and what are the factors that cause students’ difficulties in learning vocabulary. The objective of this research was to investigate and described the students’ difficulties in learning vocabulary. The research conducted in SMP Pesona Dywantara Distrik Bogor. The number of participants who selected by the writer are 10 eighth grade students of SMP Pesona Dywantara using purposive sampling. This research has two research questions, those are: (1) What are the difficulties faced by students in learning vocabulary? (2) What are the factors that cause students’ difficulties in learning vocabulary? The research design used in this research was descriptive qualitative because this research results the descriptive data in the form of written or picture data from the subjects of the research being observed. Based on the data analysis, the researcher found three difficulties faced by students. Those are; Spelling and pronunciation, words meaning and using words approperiately. Furthermore, the difficulties can be caused by many factors. They were afraid making mistake in producing certain word, never practice the vocabulary in daily communication or written practices and just studied the material in class and they did not learn at home.